Analysis of Line Efficiency in Finishing Department Pt Pura Nusapersada Unit Paper Mill 7/8 - Suhardi, Bambang; Sari, Wahyu Ani Maulidiyah (UUM Press, 2021)
Measuring line efficiency and productivity are very important to do to find out in which level the efficiency and productivity of the business process has been carried out by the company. This paper aims to determine line efficiency analysis and provide suggestions for improvements to increase line efficiency at the finishing department of PT Pura Nusapersada. Measurement of line efficiency in the finishing department of PT Pura Nusapersada paper mill unit 7 has not yet reached the company's line efficiency value target. The initial line efficiency assessment obtained a percentage of 65.14% while the company's target was 70%. In this paper, a fishbone diagram is used to determine the root cause of the problem. Based on the research results, it was found that the most dominant cause of the problem was the inefficient work elements at the cutter, sorting, pollar, and packing work stations. Improvements were made using the eliminate, combine, re-arrange, and simplify (ECRS) method and the results of the line efficiency improvements in the finishing department increased to 71.90% and the company's target can be met.